2019
DOI: 10.2174/1573396315666190625110748
|View full text |Cite
|
Sign up to set email alerts
|

New Targeted Treatments for Fragile X Syndrome

Abstract: Fragile X Syndrome (FXS) is the most common cause of inherited intellectual disability with prevalence rates estimated to be 1:5,000 in males and 1:8,000 in females. The increase of >200 Cytosine Guanine Guanine (CGG) repeats in the 5’ untranslated region of the Fragile X Mental Retardation 1 (FMR1) gene results in transcriptional silencing on the FMR1 gene with a subsequent reduction or absence of fragile X mental retardation protein (FMRP), an RNA binding protein involved in the maturation and elimination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
0
9

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(67 citation statements)
references
References 79 publications
(92 reference statements)
0
54
0
9
Order By: Relevance
“…The ongoing research on targeted treatment for FXS has shown some medications that are currently available for clinical use, such as metformin, minocycline, and sertraline. Some promising targeted treatments are still in clinical trials, including cannabidiol, ganaxolone, gaboxadol, arbaclofen, and mavoglurant, among others (31,32). Research conducted on children with FXS treated with metformin showed improvements in language development and behavior, such as mood instability and aggressive behavior in most patients (33).…”
Section: Management Of Fxs In Indonesiamentioning
confidence: 99%
“…The ongoing research on targeted treatment for FXS has shown some medications that are currently available for clinical use, such as metformin, minocycline, and sertraline. Some promising targeted treatments are still in clinical trials, including cannabidiol, ganaxolone, gaboxadol, arbaclofen, and mavoglurant, among others (31,32). Research conducted on children with FXS treated with metformin showed improvements in language development and behavior, such as mood instability and aggressive behavior in most patients (33).…”
Section: Management Of Fxs In Indonesiamentioning
confidence: 99%
“…23 Therefore, minocycline is well tolerated but requires clinical monitoring and testing for ANA and liver function. 24…”
Section: Minocyclinementioning
confidence: 99%
“…Additionally, since there are multiple pathways involved in FXS pathogenesis, a combination of medications or medications targeting multiple pathways could be more beneficial 24 . Trials involving medication and non-pharmacological interventions such as Parent Implemented Language Intervention (PILI) could also be more sustainable and beneficial.…”
Section: Challenges In the Search For A Targeted Treatment In Fxsmentioning
confidence: 99%
“…This hyperexcitability seems to be the result of an enhanced long-term depression (LTD) and reduced long-term potentiation (LTP), the contribution of both mechanisms being different according to brain regions [ 34 ]. In some patients, the absence of FMRP may also affect other classic neurochemicals pathways, including the dopaminergic, cholinergic and serotonergic-mediated pathways [ 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%